Advocating the use of risk-based online single submission (OSS) to MSMES in Sukabumi district - Alfhi Fusvita Cahya; Hardi Warsono; Kismartini Kismartini (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This research is about Risk-Based Electronically Integrated Business Licensing Service Policy Challenges by Using Online Single Submission (OSS) among MSMEs which aims to obtain licensing in Improving Good Governance at the One-Stop Integrated Service Investment Service in Sukabumi Regency. The method used in this analysis is a qualitative method using secondary data. The theory used as a reference is advocacy which consists of six steps, namely analysis, strategy, mobilization, action, evaluation, and sustainability. The results of the study show that advocacy for the use of risk-based OSS for MSMEs in the Sukabumi district has been going quite well according to PP No. 5 of 2021. However, there are still things that need to be optimized because of the obstacles encountered, including the lack of coordination and socialization between the agency and business actors, inadequate internet network in the hinterland, not all of them have computers or Android-based cell phones for can access OSS, central and regional policies are not yet fully integrated, server down occurs frequently, and OSS upgrades are still frequently carried out. Efforts that need to be made, namely by providing internet and computer facilities for business actors at the licensing service office, guiding business actors to obtain the necessary permits, conducting routine outreach to business actors who have difficulty getting access and do not understand digitization, always follow the updates on OSS developments, and so on.